Enhancement of Notch receptor maturation and signaling sensitivity by Cripto-1 - Watanabe, Kazuhide (The Rockefeller University Press, 2009)
Nodal and Notch signaling pathways play essential roles in vertebrate development. Through a yeast two-hybrid screening, we identified Notch3 as a candidate binding partner of the Nodal coreceptor Cripto-1. Coimmunoprecipitation analysis confirmed the binding of Cripto-1 with all four mammalian Notch receptors. Deletion analyses revealed that the binding of Cripto-1 and Notch1 is mediated by the Cripto-1/FRL-1/Cryptic domain of Cripto-1 and the C-terminal region of epidermal growth factor–like repeats of Notch1. Binding of Cripto-1 to Notch1 occurred mainly in the endoplasmic reticulum–Golgi network. Cripto-1 expression resulted in the recruitment of Notch1 protein into lipid raft microdomains and enhancement of the furin-like protein convertase-mediated proteolytic maturation of Notch1 (S1 cleavage). Enhanced S1 cleavage resulted in the sensitization to ligand-induced activation of Notch signaling. In addition, knockdown of Cripto-1 expression in human and mouse embryonal carcinoma cells desensitized the ligand-induced Notch signaling activation. These results suggest a novel role of Cripto-1 in facilitating the posttranslational maturation of Notch receptors.